A novel preparation of superhydrophobic silica aerogels via the combustion drying method. Issue 18 (15th September 2021) - Li, Zhonghao; Liao, Runxun; Jia, Runping; Liu, Yufeng; Xu, Xiaowei; Shen, Jun; Wang, Xiaodong; Wu, Guangming; Wu, Qingsheng; Shi, Jichao
Abstract: Silica aerogels with prominent physical, thermal, optical, and acoustic properties are considered to be highly promising materials. However, owing to the high cost and the complex production processes associated with existing drying technologies, the application of silica aerogels is limited in many fields. In this study, a novel combustion drying method (CDM) was successfully used in the synthesis of superhydrophobic silica aerogels for the first time. It was confirmed that silica aerogel prepared by CDM has a typical aerogel structure with low density, high porosity, high specific surface area, high total pore volume, superhydrophobicity and high thermal stability. Compared with supercritical fluid drying, freeze drying and ambient pressure drying, CDM possesses significant advantages in the drying efficiency and low-cost production due to its active drying mode. Finally, the mechanism of the combustion drying method is proposed based on the combustion of organic solvents. The results will be meaningful for the design and production of aerogel materials in the future.